(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: TGF-β is a key intrascleral mediator of extracellular matrix remodeling. Purpose: To investigate the pattern of allele frequency and genotype distribution for TGF-β1 gene rs1800469 among the Ukrainian Podillia region’s pediatric population with different degrees of myopia. Materials and Methods: Real-time polymerase chain reaction was used for genotyping for TGF-β1 gene rs1800469 in 105 children (210 eyes) with different degrees of myopia and 107 emmetropic children. Results: Compared to controls, significant differences in allele and genotype frequencies for the SNP under investigation were found only in the high myopia group. The presence of the C allele of TGF-β1 -509 C>T (rs1800469) was found to increase the risk for developing high myopia (OR = 2.44, 95% CI, 1.17–5.08; p = 0.02). The presence of a variant T allele was found to have an additive protective effect against developing high myopia in the CT genotype carriers (OR = 0.85, 95% CI, 0.34–2.16; p = 0.02) and TT genotype carriers (OR = 0.16; 95% CI, 0.02–1.29; p = 0.02). Conclusion: To our best knowledge, this study is the first to demonstrate that the CC genotype of rs1800469 is associated with the risk of the development of high myopia in a European population.